Factors affecting contraceptive use and non-use among military residents in Fort Bonifacio, 1975-1976 - Cabanlig, Lina A.
This is a descriptive survey of the socio-demographic variables, personal motivations, knowledge of, attitudes towards, and practices on family planning and the family building patterns of 10 of the military families in an urbanized setting. This setting was selected on the basis of the hemogeneity of the military families in terms of occupation; i.e. military service, exposure to identical health and family planning facilities, common source of income, exposure to the same urbanized setting, problems of the separation of the spouse in case the head is called for military service elsewhere, and a host of other experiences which are familiar to residents in this community. The objectives of this study are to determine the factors that account for the acceptance or non-acceptance of a family planning method. The study also aims to identify further the factors that account for the continued use and the short term use of a family planning method among the acceptors. To test the hypothesis formulated, i.e., the relationship between the different independent variables (the socio-demographic, personal motivations, knowledge of, attitudes towards and practices of family planning and the family building patterns) and the dependent variables (acceptance and non-acceptance, continuing use and dropout) was subjected to statistical analysis. The index of dissimilarity, the means and the T-test for the means were the statistical measures used. A total of 365 respondents (10 of the entire military population in the area) composed of married women in the reproductive ages of 15 to 44 years whose spouses were connected with the military service were the study subjects. Of this number, 112 were non-acceptors and 253 were acceptors. Among the acceptors, 30 were drop outs and 223 were continuing users. The subjects consisted of officers and enlisted men. Systematic random sampling was done. Every 10th household was utilized for the study sampling. Among all the socio-demographic factors probed only the mean age of the respondents differed significantly between the different groups: 32.7 years for acceptors, 31.3 for the non-acceptors while 32.9 years for continuing users and 27.5 years for drop outs. Some personal motivations were found to be significant for at least 2 groups of respondents. A majority of the acceptors (91.7 ) had interspouse discussions on the need for family planning while only (10.2 ) of the dropouts carried on such discussions. Fewer acceptors had no househelp (52.6 ) as compared to (75 ) non-acceptors had no househelp. The mean number of children preferred by the wife is 4.1 while the mean number preferred by the dropouts is 3.7. Although continuing users prefer a bigger number than the drop out, comparison of this mean number preferred with the mean number of living children will show that continuing users have more (4.4) children than they prefer to have. Drop outs however, prefer a bigger number (3.7) than the actual number of living children (3.3) they already have. It can be seen that since continuing users have more children than they prefer they probably are more persistent in contraceptive use. On the other hand, since the drop outs prefer a bigger number than they already have, it may be 1 of the reasons for their non-persistence in contraceptive use.